A Study of Syntactic Functions of More in English - Dewi Juni Artha (English Teaching and Linguistics Journal (ETLiJ), 2021)
This article is the result of a study which is concerned with syntactic functions of “more” in English. Traditionally, more refers to a unique word which functions in the comparative degree of an adjective or an adverb. Beside, the word more also functions as a modifier and a general determiner. This article consists of a brief account of the word more with its subdivisions. The main analysis focused on syntactic functions of more in English. Some syntactic data show that the word more may function as general determiner, comparative quantifier, modifier of a noun group, modifier of an adjective, modifier of an adverb, modifier of a pre-modifying adverb, and in an comparative structure